1993
DOI: 10.1055/s-0038-1649605
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Recombinant Factor VIIa in the Rat – A Comparison of Bio-, Immuno- and Isotope Assays

Abstract: SummaryRecombinant human factor VII a (rFVIIa) is an activated coagulation factor for intravenous use as a haemostatic agent in haemophiliacs who generate antibodies against factor VIII or IX. Plasma kinetic studies are important for the understanding of the action of rFVIIa which is exerted in the vascular compartment of the body, more specifically on the vessel walls at the site of injury. In the present study, rats were dosed 100 or 500 μg/kg 125I-rFVIIa i. V., without any side effects being observed, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
5
17
0
Order By: Relevance
“…At 3 and 6.5 h post injection, FVIIa plasma concentrations was 2.7 and 1.5 times higher in rats injected with PEGLip-FVIIa than in rats injected with free FVIIa. Pharmacokinetic parameters that we measured for free FVIIa are in agreement with those previously reported in rats [30].…”
Section: Discussionsupporting
confidence: 91%
“…At 3 and 6.5 h post injection, FVIIa plasma concentrations was 2.7 and 1.5 times higher in rats injected with PEGLip-FVIIa than in rats injected with free FVIIa. Pharmacokinetic parameters that we measured for free FVIIa are in agreement with those previously reported in rats [30].…”
Section: Discussionsupporting
confidence: 91%
“…The lifetime of the mutant appeared normal, with approximately 50% of the activity remaining after 100 min. This result is similar and, in some cases, longer than the circulation time of other vitamin K-dependent proteins and enzymes (30,31).…”
Section: Resultssupporting
confidence: 59%
“…FVII has the shortest half-life, approximately 5 hours in humans, 2,3 and recent studies with recombinant activated FVII (FVIIa) showed a similar half-life in adults. 4,5 Thus, the half-life of FVIIa antigen appears to be similar to that of zymogen FVII, and this finding is in agreement with results obtained in studies in rats 6,7 and mice. 8 In addition, data from mice showed that the half-life of FVIIa antigen was not significantly affected by occupancy of the active site with a low-molecular weight inhibitor or by macromolecular inhibitor (antithrombin) complex formation.…”
Section: Introductionsupporting
confidence: 90%